Lectotypification of five subspecies names of Hieracium auriculoides and H. brachiatum (Asteraceae) described from the North Caucasus by D.I. Litvinov and K.H. Zahn - Shiyan, N.M.; Pavlenko-Barysheva, V.S.; Tatanov, I.V. (Український ботанічний журнал, 2017)
Five names of subspecies of Hieracium s.l. (Asteraceae) described from the North Caucasus by D.I. Litvinov and K.H. Zahn are lectotypified: Hieracium auriculoides Láng subsp. basileucum Litv. et Zahn, H. auriculoides subsp. sabiniceps Litv. et Zahn (≡ H. auriculoides subsp. sabinocephalum Litv. et Zahn, nom. illeg.), H. auriculoides subsp. sublasiophorum Litv. et Zahn, H. auriculoides subsp. umbelliforme Litv. et Zahn (≡ H. auriculoides subsp. subumbelliforme Zahn, nom. illeg.; H. subumbelliforme Üksip), and H. brachiatum Bertero ex DC. subsp. alticaule Litv. et Zahn. For each subspecies, the following data are provided: basionym, main synonyms, information about type localities according to the protologue, lectotype (isolectotypes, syntypes, if applicable) and their herbarium barcodes, and nomenclatural notes. In addition, scanned images of all newly designated lectotypes are presented. Лектотипіфіковано назви п'яти підвидів Hieracium s.l. (Asteraceae), описаних Д.І. Литвиновим та К.Г. Цаном з Північного Кавказу: Hieracium auriculoides Láng subsp. basileucum Litv. et Zahn, H. auriculoides subsp. sabiniceps Litv. et Zahn (≡ H. auriculoides subsp. sabinocephalum Litv. et Zahn, nom. illeg.), H. auriculoides subsp. sublasiophorum Litv. et Zahn, H. auriculoides subsp. umbelliforme Litv. et Zahn (≡ H. auriculoides subsp. subumbelliforme Zahn, nom. illeg.; H. subumbelliforme Üksip) і H. brachiatum Bertero ex DC. subsp. alticaule Litv. et Zahn. Для кожного підвиду наведені: базионім, основні синоніми, інформація про тип за протологом, лектотип, ізолектотип, синтип(и) та їхні баркод(и) відповідного Гербарію; подаються номенклатурні нотатки. Подані зображення (скани) усіх п'яти лектотипів, зазначених у статті. Лектотипифицированны названия пяти подвидов Hieracium s.l. (Asteraceae), описанных Д.И. Литвиновым и К.Г. Цаном с Северного Кавказа: Hieracium auriculoides Láng subsp. basileucum Litv. et Zahn, H. auriculoides subsp. sabiniceps Litv. et Zahn (≡ H. auriculoides subsp. sabinocephalum Litv. et Zahn, nom. illeg.), H. auriculoides subsp. sublasiophorum Litv. et Zahn, H. auriculoides subsp. umbelliforme Litv. et Zahn (≡ H. auriculoides subsp. subumbelliforme Zahn, nom. illeg.; H. subumbelliforme Üksip) и H. brachiatum Bertero ex DC. subsp. alticaule Litv. et Zahn. Для каждого подвида указаны: базионим, основные синонимы, информация о типе по протологу, лектотип, изолектотип, синтип(ы) и их баркод(ы) в соответствующем Гербарии; приведены номенклатурные примечания. Даны изображения (сканы) всех пяти лектотипов, обозначенных в статье.